MODEL TRANSAKSI BERBASIS FINTECH SYARIAH PERSPEKTIF FIKIH MUAMALAH - Muhammad Sauqi; Alya Rohani; Mar’atun Solehah (Jurnal Syariah dan Ekonomi Islam, 2025)
The development of information and communication technology, the financial industry has undergone changes for the digital revolution, triggered by the presence of fintech (financial technology). Sharia fintech, as a special variant in the digital financial ecosystem, presents a breakthrough in financial services that are in line with Islamic ethical values. The discovery of sharia-based fintech businesses not only offers transaction solutions that are in accordance with sharia principles, but also plays a strategic role in opening wider financial access for the community. Fiqh muamalah is a branch of science that regulates social relations and economic transactions in the Muslim community. Using the development of technology, especially in the financial sector, the emergence of sharia fintech as an interesting phenomenon to study. The rapid development of technology forms processes in the financial sector that are also developing. This incident makes it easier for residents to get financing, especially for business capital or to maintain the continuity of the business they are running. The purpose of this study is to study how to apply the principles of fiqh muamalah in the sharia fintech business model. The research used uses a qualitative research method with a literature study method and a case study.